Economic Earthquake Resistance Construction of High-Rise Buildings - Ranjan, Raushan; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
The economic perception of earthquake resistance construction for medium- to high-rise RCC buildings is examined in this paper. The conventional way of creating high-rise buildings is not financially viable without a shear wall to withstand seismic energy. Framed structures with irregular floor plans that vary in size, shape, and geometry are also expensive. Many studies have been conducted recently on the Coupling Ratio (CR). The current analysis investigates the behavior of the coupled shear wall and the CR for an affordable earthquake resistance construction including the shear wall within a range of 30 % to 45 %. The study shows that shear walls could be reduced at 40–50 % and at 60–70 % of the base height for regular and irregular buildings, respectively. The current study also comes to the conclusion that coupled shear wall earthquake-resistant construction is more practical than the conventional approach because couple beams can be repaired with ease.